Inflation Expectations as a Policy Tool? - Olivier Coibion; Yuriy Gorodnichenko; Saten Kumar; Mathieu Pedemonte (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2018)
We assess whether central banks may use inflation expectations as a policy tool for stabilization purposes. We review recent work on how expectations of agents are formed and how they affect their economic decisions. Empirical evidence suggests that inflation expectations of households and firms affect their actions but the underlying mechanisms remain unclear, especially for firms. Two additional limitations prevent policy-makers from being able to actively manage inflation expectations. First, available surveys of firms' expectations are systematically deficient, which can only be addressed through the creation of large, nationally representative surveys of firms. Second, neither households' nor firms' expectations respond much to monetary policy announcements in low-inflation environments. We provide suggestions for how monetary policy-makers can pierce this veil of inattention through new communication strategies. At this stage, there remain a number of implementation issues and open research questions that need to be addressed to enable central banks to use inflation expectations as a policy tool.
Keywords: E31; C83; D84; 330; survey; inflation expectations; firms; managers